Skip to content
Related Articles

Related Articles

Improve Article

Class 12 RD Sharma Solutions – Chapter 7 Adjoint and Inverse of a Matrix – Exercise 7.1 | Set 3

  • Last Updated : 28 Mar, 2021

Question 25. Show that the matrix A = \begin{bmatrix}1&0&-2\\-2&-1&2\\3&4&1\end{bmatrix}  satisfies the equation A3 – A2 – 3A – I3 = 0. Hence, find A-1.

Solution:

Here, A = \begin{bmatrix}1&0&-2\\-2&-1&2\\3&4&1\end{bmatrix}

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12. 

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.

A2\begin{bmatrix}1&0&-2\\-2&-1&2\\3&4&1\end{bmatrix}  \begin{bmatrix}1&0&-2\\-2&-1&2\\3&4&1\end{bmatrix}=  \begin{bmatrix}-5&-8&-4\\6&9&4\\-2&0&3\end{bmatrix}



A3\begin{bmatrix}-5&-8&-4\\6&9&4\\-2&0&3\end{bmatrix}  \begin{bmatrix}1&0&-2\\-2&-1&2\\3&4&1\end{bmatrix}=  \begin{bmatrix}-1&-8&-10\\0&7&10\\7&12&7\end{bmatrix}

Now A3 – A2 – 3A – I3 \begin{bmatrix}-1&-8&-10\\0&7&10\\7&12&7\end{bmatrix}-\begin{bmatrix}-5&-8&-4\\6&9&4\\-2&0&3\end{bmatrix}-3\begin{bmatrix}1&0&-2\\-2&-1&2\\3&4&1\end{bmatrix}-\begin{bmatrix}1&0&0\\0&1&0\\0&0&1\end{bmatrix}

=\begin{bmatrix}-1+5-3-1&-8+8&-10+4+6\\-6+6&7-9+3-1&10-4-6\\7+2-9&12-12&7-3-3-1\end{bmatrix}

\begin{bmatrix}0&0&0\\0&0&0\\0&0&0\end{bmatrix}=O

So, A3 – A2 – 3A – I3 = 0

⇒ A-1(AAA) – A-1(AA) – 3A-1A – A-1I = 0

⇒ A2 – A – 3I – A-1 = 0

⇒ A-1 = A2 – A – 3I



\begin{bmatrix}-5&-8&-4\\6&9&4\\-2&0&3\end{bmatrix} - \begin{bmatrix}1&0&-2\\-2&-1&2\\3&4&1\end{bmatrix}-  \begin{bmatrix}3&0&0\\0&3&0\\0&0&3\end{bmatrix}

Therefore, A-1 =\begin{bmatrix}-9&-8&-2\\8&7&2\\-5&-4&-1\end{bmatrix}

Question 26. If A = \begin{bmatrix}2&-1&1\\-1&2&-1\\1&-1&2\end{bmatrix} . Verify that A3 – 6A2 + 9A – 4I = O and hence find A-1.

Solution:

Here, A = \begin{bmatrix}2&-1&1\\-1&2&-1\\1&-1&2\end{bmatrix}

A2\begin{bmatrix}2&-1&1\\-1&2&-1\\1&-1&2\end{bmatrix}    \begin{bmatrix}2&-1&1\\-1&2&-1\\1&-1&2\end{bmatrix}

=\begin{bmatrix}4+1+1&-2-2-1&2+1+2\\-2-2-1&1+4+1&-1-2-2\\2+1+2&-1-2-2&1+1+4\end{bmatrix}

\begin{bmatrix}6&-5&5\\-5&6&-5\\5&-5&6\end{bmatrix}

A3 = A2A = \begin{bmatrix}6&-5&5\\-5&6&-5\\5&-5&6\end{bmatrix} \begin{bmatrix}2&-1&1\\-1&2&-1\\1&-1&2\end{bmatrix}

\begin{bmatrix}12+5+5&-6-10-5&6+5+10\\-10-6-5&5+12+5&-5-6-10\\10+5+6&-5-10-6&5+5+12\end{bmatrix}

\begin{bmatrix}22&-21&21\\-21&22&-21\\21&-21&22\end{bmatrix}



Now, A3 – 6A2 + 9A – 4I

\begin{bmatrix}22&-21&21\\-21&22&-21\\21&-21&22\end{bmatrix}-6  \begin{bmatrix}6&-5&5\\-5&6&-5\\5&-5&6\end{bmatrix}+9  \begin{bmatrix}2&-1&1\\-1&2&-1\\1&-1&2\end{bmatrix}-4  \begin{bmatrix}1&0&0\\0&1&0\\0&0&1\end{bmatrix}

\begin{bmatrix}22&-21&21\\-21&22&-21\\21&-21&22\end{bmatrix}-\begin{bmatrix}36&-30&30\\-30&30&-30\\30&-30&36\end{bmatrix}+\begin{bmatrix}18&-9&9\\-9&18&-9\\9&-9&18\end{bmatrix}-\begin{bmatrix}4&0&0\\0&4&0\\0&0&4\end{bmatrix}

\begin{bmatrix}40&-30&30\\-30&40&-30\\30&-30&40\end{bmatrix}-\begin{bmatrix}40&-30&30\\-30&40&-30\\30&-30&40\end{bmatrix}

\begin{bmatrix}0&0&0\\0&0&0\\0&0&0\end{bmatrix}=O

So, A3 – 6A2 + 9A – 4I = O

Multiplying both side by A-1

⇒ A-1(AAA) – 6A-1(AA) 9A-1A – 4A-1I = O

⇒ AAI – 6AI + 9I = 4A-1

⇒ 4A-1 = A2I – 6AI + 9I



=\begin{bmatrix}6&-5&5\\-5&6&-5\\5&-5&6\end{bmatrix}-6  \begin{bmatrix}2&-1&1\\-1&2&-1\\1&-1&2\end{bmatrix}+9  \begin{bmatrix}1&0&0\\0&1&0\\0&0&1\end{bmatrix}

=\begin{bmatrix}6&-5&5\\-5&6&-5\\5&-5&6\end{bmatrix}-\begin{bmatrix}12&-6&6\\-6&12&-6\\6&-6&12\end{bmatrix}+\begin{bmatrix}9&0&0\\0&9&0\\0&0&9\end{bmatrix}

=\begin{bmatrix}3&1&-1\\1&3&1\\-1&1&3\end{bmatrix}

⇒ A-1 \frac{1}{4}\begin{bmatrix}3&1&-1\\1&3&1\\-1&1&3\end{bmatrix}

Question 27. If A =\frac{1}{9}\begin{bmatrix}-8&1&4\\4&4&7\\1&-8&4\end{bmatrix} , prove that A-1 = AT.

Solution:

Here, A = \frac{1}{9}\begin{bmatrix}-8&1&4\\4&4&7\\1&-8&4\end{bmatrix}

AT\frac{1}{9}\begin{bmatrix}-8&4&1\\1&4&-8\\4&7&4\end{bmatrix}

Now, Finding A-1

|A| = 1/9[-8(16 + 56) – 1(16 – 7) + 4(-32 – 4)]

= -81



 Therefore, inverse of A exists

Cofactors of A are:

C11 = 72      C12 = -9       C13 = -36

C21 = -36    C22 = -36    C23 = -63

C31 = -9      C32 = 72      C33 = -36

adj A = \begin{bmatrix}C_{11}&C_{12}&C_{13}\\C_{21}&C_{22}&C_{23}\\C_{31}&C_{32}&C_{34}\end{bmatrix}^T    

=\begin{bmatrix}72&-9&-36\\-36&-36&-63\\-9&72&-36\end{bmatrix}^T

=\begin{bmatrix}72&-36&-9\\-9&-36&72\\-36&-63&-36\end{bmatrix}

A-1 = 1/|A|. adj A

Hence, A-1\frac{1}{-81}\begin{bmatrix}72&-36&-9\\-9&-36&72\\-36&-63&-36\end{bmatrix}



\frac{1}{9}\begin{bmatrix}-8&4&1\\1&4&-8\\4&7&4\end{bmatrix}     

= AT 

Hence Proved   

Question 28. If A = \begin{bmatrix}3&-3&4\\2&3&4\\0&-1&1\end{bmatrix} , show that A-1 = A3.

Solution:

Here, A = \begin{bmatrix}3&-3&4\\2&3&4\\0&-1&1\end{bmatrix}

|A| = 3(-3 + 4) + 3(2 – 0) + 4(-2 – 0)

= 3 + 6 – 8

= 1 

Therefore, inverse of A exists

Cofactors of A are:

C11 = 1      C12 = -2     C13 = -2

C21 = -1    C22 = 3      C23 = 3

C31 = 0     C32 = -4     C33 = -3

adj A =\begin{bmatrix}1&-1&0\\-2&3&-4\\-2&3&-3\end{bmatrix}

A-1= 1/|A|. adj A

\frac{1}{1}\begin{bmatrix}1&-1&0\\-2&3&-4\\-2&3&-3\end{bmatrix}

Now, A2\begin{bmatrix}3&-3&4\\2&3&4\\0&-1&1\end{bmatrix}\begin{bmatrix}3&-3&4\\2&3&4\\0&-1&1\end{bmatrix}

=\begin{bmatrix}3&-4&4\\0&-1&0\\-2&2&-3\end{bmatrix}

A3\begin{bmatrix}3&-4&4\\0&-1&0\\-2&2&-3\end{bmatrix}\begin{bmatrix}3&-3&4\\2&3&4\\0&-1&1\end{bmatrix}

=\begin{bmatrix}1&-1&0\\-2&3&-4\\-2&3&-3\end{bmatrix}



= A-1 

Hence Proved

Question 29. If A =\begin{bmatrix}-1&2&0\\-1&1&1\\0&1&0\end{bmatrix} , show that A2 = A-1.

Solution: 

Here, A = \begin{bmatrix}-1&2&0\\-1&1&1\\0&1&0\end{bmatrix}

LHS = A2

\begin{bmatrix}-1&2&0\\-1&1&1\\0&1&0\end{bmatrix}\begin{bmatrix}-1&2&0\\-1&1&1\\0&1&0\end{bmatrix}

\begin{bmatrix}-1&0&2\\0&0&1\\-1&1&2\end{bmatrix}

|A| = -1(1 – 0) – 2(-1 – 0) + 0

= 1

Therefore, inverse of A exists

Cofactors of A are:

C11 = -1     C12 = 0     C13 = -1

C21 = 0      C22 = 0     C23 = 1

C31 = 21    C32 = 1      C33 = 1

adj A = \begin{bmatrix}-1&0&-1\\0&0&1\\2&1&1\end{bmatrix}^T

=\begin{bmatrix}-1&0&2\\0&0&1\\-1&1&1\end{bmatrix}

A-1 = 1/|A|. adj A

Hence, A-1\frac{1}{1}\begin{bmatrix}-1&0&2\\0&0&1\\-1&1&1\end{bmatrix}

=\begin{bmatrix}-1&0&2\\0&0&1\\-1&1&1\end{bmatrix}

= A



Hence Proved

Question 30. Solve the matrix equation\begin{bmatrix}5&4\\1&1\end{bmatrix}X = \begin{bmatrix}1&-2\\1&3\end{bmatrix} , where X is a 2×2 matrix.

Solution:

We have, \begin{bmatrix}5&4\\1&1\end{bmatrix}X = \begin{bmatrix}1&-2\\1&3\end{bmatrix}

Let A = \begin{bmatrix}5&4\\1&1\end{bmatrix}     and B = \begin{bmatrix}1&-2\\1&3\end{bmatrix}

So. AX = B

⇒ X = A-1B

Now, |A| = 5 – 4 = 1 

Co factors of A are:

C11 = 1         C12 = -1

C21 = -4      C22 = 5

adj A = \begin{bmatrix}1&-1\\-4&5\end{bmatrix}^T

=\begin{bmatrix}1&-4\\1&5\end{bmatrix}

A-1\begin{bmatrix}1&-4\\1&5\end{bmatrix}

Therefore, X = \begin{bmatrix}1&-4\\1&5\end{bmatrix}\begin{bmatrix}1&-2\\1&3\end{bmatrix}

X = \begin{bmatrix}-3&-14\\4&17\end{bmatrix}

Question 31. Find the matrix X satisfying the matrix equation: X\begin{bmatrix}5&3\\-1&-2\end{bmatrix}=\begin{bmatrix}14&7\\7&7\end{bmatrix} .

Solution:

We have, \begin{bmatrix}5&3\\-1&-2\end{bmatrix}=\begin{bmatrix}14&7\\7&7\end{bmatrix}

Let A = \begin{bmatrix}5&3\\-1&-2\end{bmatrix}    and B = \begin{bmatrix}14&7\\7&7\end{bmatrix}

So, XA = B

XAA-1 = BA-1



XI = BA-1 ………..(i)  

Now, |A| = -7

Co factors of A are:

C11 = -2       C12 = 1

C21 = -3      C22 = 5

adj A = \begin{bmatrix}-2&1\\-3&5\end{bmatrix}^T

=\begin{bmatrix}-2&-3\\1&5\end{bmatrix}

A-1 = 1/|A|.adj (A)

=\frac{1}{(-7)}\begin{bmatrix}-2&-3\\1&5\end{bmatrix}=\frac{-1}{7} \begin{bmatrix}2&3\\-1&-5\end{bmatrix}

Therefore, X = \begin{bmatrix}14&7\\7&7\end{bmatrix} .1/7.\begin{bmatrix}2&3\\-1&-5\end{bmatrix}

=\frac{7}{7}\begin{bmatrix}2&1\\1&1\end{bmatrix} \begin{bmatrix}2&3\\-1&-5\end{bmatrix}

X = \begin{bmatrix}3&1\\1&-2\end{bmatrix}

Question 32. Find the matrix X for which: \begin{bmatrix}3&2\\7&5\end{bmatrix} X\begin{bmatrix}-1&1\\-1&1\end{bmatrix}=\begin{bmatrix}2&-1\\0&4\end{bmatrix}

Solution:

Let, A = \begin{bmatrix}3&2\\7&5\end{bmatrix}

B = \begin{bmatrix}-1&1\\-2&1\end{bmatrix}

C = \begin{bmatrix}2&-1\\0&4\end{bmatrix}

 Then the given equation becomes

 A × B = C

⇒ X = A-1CB-1

Now |A| = 35 -14 = 21



|B| = -1 + 2 = 1

A-1 = adj (A)/|A| = \frac{1}{21}\begin{bmatrix}5&-2\\-7&3\end{bmatrix}

B-1 = adj (B)/|A| = \begin{bmatrix}1&-1\\2&-1\end{bmatrix}

X = A-1 CB-1\frac{1}{21}\begin{bmatrix}5&-2\\-7&3\end{bmatrix} \begin{bmatrix}2&-1\\0&4\end{bmatrix} \begin{bmatrix}1&-1\\2&-1\end{bmatrix}

\begin{bmatrix}-16&3\\24&-5\end{bmatrix}

Question 33. Find the matrix X satisfying the equation:\begin{bmatrix}2&1\\5&3\end{bmatrix}X\begin{bmatrix}5&3\\3&2\end{bmatrix}=\begin{bmatrix}1&0\\0&1\end{bmatrix}

Solution:

Let A = \begin{bmatrix}2&1\\5&3\end{bmatrix}   B = \begin{bmatrix}5&3\\3&2\end{bmatrix}

AXB = I

X = A-1B-1

|A| = 6 – 5 = 1



|B| = 10 – 9 = 1

A-1 = adj A /|A| = \begin{bmatrix}3&-1\\-5&2\end{bmatrix}

B-1 = adj B/|B| = \begin{bmatrix}2&-3\\-3&5\end{bmatrix}

X = \begin{bmatrix}3&-1\\-5&2\end{bmatrix}\begin{bmatrix}2&-3\\-3&5\end{bmatrix}

\begin{bmatrix}9&-14\\-16&25\end{bmatrix}   

Question 34. If A = \begin{bmatrix}1&2&2\\2&1&2\\2&2&1\end{bmatrix} , Find A-1 and prove that A2 – 4A – 5I = O.

Solution:

Here, A = \begin{bmatrix}1&2&2\\2&1&2\\2&2&1\end{bmatrix}

A2\begin{bmatrix}1&2&2\\2&1&2\\2&2&1\end{bmatrix}  \begin{bmatrix}1&2&2\\2&1&2\\2&2&1\end{bmatrix}

\begin{bmatrix}9&8&8\\8&9&8\\8&8&9\end{bmatrix}

Now, A2 + 4A – 5I

\begin{bmatrix}9&8&8\\8&9&8\\8&8&9\end{bmatrix}-4\begin{bmatrix}1&2&2\\2&1&2\\2&2&1\end{bmatrix}-\begin{bmatrix}5&0&0\\0&5&0\\0&0&5\end{bmatrix}

\begin{bmatrix}0&0&0\\0&0&0\\0&0&0\end{bmatrix}= 0

Now, A2 – 4A – 5I = O

⇒ A-1AA – 4A-1A – 5A-1I = O 

⇒ 5A-1 = [A – 4I]

\begin{bmatrix}1&2&2\\2&1&2\\2&2&1\end{bmatrix}-\begin{bmatrix}4&0&0\\0&4&0\\0&0&4\end{bmatrix}

\begin{bmatrix}-3&2&2\\2&-3&2\\2&2&-3\end{bmatrix}

 A-1 \frac{1}{5}\begin{bmatrix}-3&2&2\\2&-3&2\\2&2&-3\end{bmatrix}

Question 35. If A is a square matrix of order n, prove that |A adj A| = |A|n.

Solution:

Given, |A adj A| = |A|n



Taking LHS = |A Adj A|

= |A| |Adj A| 

= |A| |A|n-1

= |A|n-1+1

= |A|n = RHS 

Hence Proved

Question 36. If A-1\begin{bmatrix}3&-1&1\\-15&6&-5\\5&-2&2\end{bmatrix}  and B = \begin{bmatrix}1&2&-2\\-1&3&0\\0&-2&1\end{bmatrix} , find (AB)-1.

Solution:

Here, B = \begin{bmatrix}1&2&-2\\-1&3&0\\0&-2&1\end{bmatrix}

|B| = 1(3 – 0) – 2(-1 – 0) – 2(2 – 0)

= 3 + 2 – 4 = 1

Therefore, inverse of B exists

Cofactors of B are:

C11 = 3       C12 = 1      C13 = 2

C21 = 2      C22 = 1      C23 = 2

C31 = 6     C32 = 2      C33 = 5

adj A = \begin{bmatrix}3&1&2\\2&1&2\\6&2&5\end{bmatrix}^T    

\begin{bmatrix}3&2&6\\1&1&2\\2&2&5\end{bmatrix}

Therefore,

B-1 \begin{bmatrix}3&2&6\\1&1&2\\2&2&5\end{bmatrix}

Hence, (AB)-1 = B-1A-1

\begin{bmatrix}3&2&6\\1&1&2\\2&2&5\end{bmatrix}\begin{bmatrix}3&-1&1\\-15&6&-5\\5&-2&2\end{bmatrix}

\begin{bmatrix}9&-3&5\\-2&1&0\\61&-24&22\end{bmatrix}        

Question 37. If A = \begin{bmatrix}1&-2&3\\0&-1&4\\-2&2&1\end{bmatrix} , find (AT)-1.

Solution:

Assuming B = AT\begin{bmatrix}1&0&-2\\-2&-1&2\\3&4&1\end{bmatrix}

|B| = 1(-1 – 8) – 0 – 2(-8 + 3)

= -9 + 10 = 1

Therefore, inverse of B exists

Cofactors of B are:

C11 = -9      C12 = 8      C13 = -5

C21 = -8     C22 = 7      C23 = -4



C31 = -2     C32 = 2      C33 = -1

adj B = \begin{bmatrix}-9&8&-5\\-8&7&-4\\-2&2&-1\end{bmatrix}^T

=\begin{bmatrix}-9&-8&-2\\8&7&2\\-5&-4&-1\end{bmatrix}

B-1\frac{1}{1}\begin{bmatrix}-9&-8&-2\\8&7&2\\-5&-4&-1\end{bmatrix}

or (AT)-1\begin{bmatrix}-9&-8&-2\\8&7&2\\-5&-4&-1\end{bmatrix}

Question 38. Find the adjoint of the matrix A = \begin{bmatrix}-1&-2&-2\\2&1&-2\\2&-2&1\end{bmatrix}  and hence show that A (adj A) = |A|I3.

Solution:

Here, A = \begin{bmatrix}-1&-2&-2\\2&1&-2\\2&-2&1\end{bmatrix}

|A| = -1(1 – 4) – 2(2 + 4) – 2(-4 – 2)

= 3 + 12 + 12 = 27

Therefore, inverse of A exists

Cofactors of A are:

C11 = -3     C12 = -6      C13 = -6

C21 = 6      C22 = 3       C23 = -6

C31 = 6      C32 = -6      C33 = 3

adj A = \begin{bmatrix}-3&-6&-6\\6&3&-6\\6&-6&3\end{bmatrix}^T

\begin{bmatrix}-3&6&6\\-6&3&-6\\-6&-6&3\end{bmatrix}

A (adj A) = \begin{bmatrix}-1&-2&-2\\2&1&-2\\2&-2&1\end{bmatrix}\begin{bmatrix}-3&6&6\\-6&3&-6\\-6&-6&3\end{bmatrix}

\begin{bmatrix}27&0&0\\0&27&0\\0&0&27\end{bmatrix}

or A (adj A) = 27\begin{bmatrix}1&0&0\\0&1&0\\0&0&1\end{bmatrix}

Hence, A (adj A) = |A|I



Hence Proved

Question 39. If A = \begin{bmatrix}0&1&1\\1&0&1\\1&1&0\end{bmatrix} , A-1 and show that A-1 = 1/2(A2 – 3I).

Solution:

Here, A = \begin{bmatrix}0&1&1\\1&0&1\\1&1&0\end{bmatrix}

|A| = 0 – 1(0 – 1) + 1(1 – 0)

= 1 + 1 = 2

Therefore, inverse of A exists

Cofactors of A are:

C11 = -1     C12 = 1      C13 = 1

C21 = 1      C22 = -1    C23 = 1

C31 = 1      C32 = 1      C33 = -1

adj A = \begin{bmatrix}-1&1&1\\1&-1&1\\1&1&-1\end{bmatrix}^T

\begin{bmatrix}-1&1&1\\1&-1&1\\1&1&-1\end{bmatrix}

A-1 = 1/|A|. adj A

Hence, A-1\frac{1}{2}\begin{bmatrix}-1&1&1\\1&-1&1\\1&1&-1\end{bmatrix}    

Now, A2 – 3I = \begin{bmatrix}0&1&1\\1&0&1\\1&1&0\end{bmatrix}\begin{bmatrix}0&1&1\\1&0&1\\1&1&0\end{bmatrix}-3\begin{bmatrix}1&0&0\\0&1&0\\0&0&1\end{bmatrix}               

=\begin{bmatrix}2&1&1\\1&2&1\\1&1&2\end{bmatrix}-\begin{bmatrix}3&0&0\\0&3&0\\0&0&3\end{bmatrix}

=\begin{bmatrix}-1&1&1\\1&-1&1\\1&1&-1\end{bmatrix}

Hence, A-1 = 1/2(A2 – 3I) 

Hence Proved




My Personal Notes arrow_drop_up
Recommended Articles
Page :